2011
DOI: 10.1177/1469787410387724
|View full text |Cite
|
Sign up to set email alerts
|

Students’ experiences of active engagement through cooperative learning activities in lectures

Abstract: This article reports on students’ experiences of lectures which included many opportunities for active engagement through cooperative learning activities. At the end of a 13-week semester-long unit, 113 students completed a questionnaire which contained five open-ended questions focusing on the extent to which the students thought that the lecture activities helped them to learn and understand the course content and to maintain their interest and attention during the sessions. Results indicate that students va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
170
0
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(188 citation statements)
references
References 18 publications
8
170
0
10
Order By: Relevance
“…But given the multiple learning benefits that group work is believed to generate, it makes sense to devise measures which enable students to fully exploit those benefits. Among these measures, Cavanagh (2011), Frederick (1993 and Wingate et al (2011) show that it is quite possible and effective to integrate collaborative learning activities and active involvement opportunities into lectures. This practice is likely to help allay students' uncertainty about group work because it merges autonomous and collaborative learning (Zepke & Leach, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But given the multiple learning benefits that group work is believed to generate, it makes sense to devise measures which enable students to fully exploit those benefits. Among these measures, Cavanagh (2011), Frederick (1993 and Wingate et al (2011) show that it is quite possible and effective to integrate collaborative learning activities and active involvement opportunities into lectures. This practice is likely to help allay students' uncertainty about group work because it merges autonomous and collaborative learning (Zepke & Leach, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to try to make group work successful, effective and enjoyable for learners, some form of guidance and support from an instructor is always needed (Cavanagh, 2011;Frederick, 1993;Hillyard et al, 2010;Hirvela, 1999;Scott-Ladd & Chan, 2008;Shimazoe & Aldrich, 2010;Storch, 2002Storch, , 2005Wingate et al, 2011;Leach & Zepke, 2011;Zepke & Leach, 2010). More specifically, Frederick (1993) points out that it is ultimately the instructor's responsibility to motivate and actively involve learners in their learning.…”
Section: Role Of Instructor In Group-based Learningmentioning
confidence: 99%
“…In particular, research on the use of active learning techniques in classroom instruction-incorporation of problem-based learning, collaborative and cooperative activities-has been found to increase student motivation to learn, student engagement and improved learning (Ahlfeldt, Mehta, & Sellnow, 2005;Cavanagh, 2011;Cherney, 2008;Hake, 1998;Kuh, 2009;Prince, 2004;Terenzini et al, 2001;Yoder & Hochevar, 2005). Research has also shown that instructors who communicate high expectations for student learning and engagement and develop courses that reflect and support those expectations can promote deep approaches to learning (Baeten, Kyndt, Struyven, & Dochy, 2010;Entwistle & McClune, 2004;Fyrenius, Wirell, & Silen, 2007).…”
Section: Level Of Academic Challengementioning
confidence: 99%
“…An increase of student engagement with course content leads to a deeper understanding of the subject. In addition to knowledge, it embraces values, including emotions, feelings and attitudes [4]. This is a crucial aspect for designers whose 'subjects' are the users that they provide quality environments for.…”
Section: Exploring Older Adults' Relationship To Their Homes Through mentioning
confidence: 99%